2010
DOI: 10.1161/circresaha.110.216713
|View full text |Cite
|
Sign up to set email alerts
|

EH Domain Proteins Regulate Cardiac Membrane Protein Targeting

Abstract: Rationale: Cardiac membrane excitability is tightly regulated by an integrated network of membrane-associated ion channels, transporters, receptors, and signaling molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 36 publications
4
71
0
Order By: Relevance
“…siRNA-siRNA recognizing PP2A/A, PP2A/C, PPP2R3A, PPP2R4, PPP2R5C, and PPP2R5E (siGENOME, Dharmacon) were individually transfected into neonatal cardiomyocytes using Effectene (39).…”
Section: Methodsmentioning
confidence: 99%
“…siRNA-siRNA recognizing PP2A/A, PP2A/C, PPP2R3A, PPP2R4, PPP2R5C, and PPP2R5E (siGENOME, Dharmacon) were individually transfected into neonatal cardiomyocytes using Effectene (39).…”
Section: Methodsmentioning
confidence: 99%
“…Vectors were completely sequenced. RNA was isolated and processed for RT-PCR as described previously, using oligo-dT to prime for cDNA production (71). Primers to identify βIV-spectrin transcripts in heart and brain include primers directed against the N terminus to recognize full-length βIVΣ1-spectrin in rat (forward, 5′-GGGATGGCTTT-GTCCTCACCC-3′; reverse, 5′-GCCAAGAGTTCCAACTTCTCC-3′; nucleotides 271-1,226 in rat [βIV-spectrin-Spnb4; XM_218364], product shown in Figure 2) as well as C-terminal primers that recognize βIVΣ1-spectrin and βIVΣ6-spectrin in mouse (βIV-spectrin-Spnb4; NM_032610) and rat (forward, 5′-CCACGATCGAGAAACTCAAGG-3′; reverse, 5′-GGTGTCCGTC-GTGTCCAACG-3′; not shown).…”
Section: Computational Analysis Of Putativementioning
confidence: 99%
“…EHD1 and EHD4 null mice both exhibit defects in spermatogenesis and decreased male fertility (George et al , 2010; Rainey et al , 2010). siRNA reduction of EHD3 in cardiomyocytes indicated that EHD3 has a role in the trafficking of the cardiac ankyrin-B membrane protein (Gudmundsson et al , 2010). In addition, EHD3 and EHD4 were sufficiently elevated following myocardial infarction, suggesting that these molecules may have a role in cardiomyocyte damage response.…”
Section: Ferlin Proteins In Cytoskeletal Rearrangements During Myomentioning
confidence: 99%